Controlled transscleral drug delivery formulations to the eye: establishing new concepts and paradigms in ocular anti-inflammatory therapeutics and antibacterial prophylaxis - Paganelli, Fernando; Cardillo, Jose A.; Dare, Alessandro R. J.; Melo, Luiz A. S.; Lucena, David R.; Silva, Arnobio A. [UNESP]; Oliveira, Anselmo Gomes de [UNESP]; Pizzolitto, Antonio Carlos [UNESP]; Lavinsky, Daniel; Skaf, Mirian; Souza-Filho, Acacio A.; Hofling-Lima, Ana L.; et al. (Informa Healthcare, 2010)
Importance of the field: The use of topical agents poses unique and challenging hurdles for drug delivery. Topical steroids effectively control ocular inflammation, but are associated with the well-recognized dilemma of patient compliance. Although administration of topical antimicrobials as prophylaxis is acceptable among ophthalmologists, this common practice has no sound evidence base Developing a new antimicrobial agent or delivery strategy with enhanced penetration by considering the anatomical and physiological constraints exerted by the barriers of the eye is not a commonly perceived strategy. Exploiting the permeability of the sclera, subconjunctival routes may offer a promising alternative for enhanced drug delivery and tissue targeting.Area covered in this review: Ocular drug delivery strategies were reviewed for ocular inflammation and infections clinically adopted for newer class of antimicrobials, which use a multipronged approach to limit risks of endophthalmitis.What the reader will gain: The analysis substantiates a new transscleral drug delivery therapeutic approach for cataract surgery.Take home message: A new anti-inflammatory and anti-infective paradigm that frees the patient from the nuisance of topical therapeutics is introduced, opening a large investigative avenue for future improved therapies.
Keywords: antibiotics; antimicrobials; cataract surgery; endophthalimitis; eye drops; eye infections; intraocular penetration; ocular drug delivery